2013
DOI: 10.1007/s00464-013-3064-7
|View full text |Cite
|
Sign up to set email alerts
|

Urgent laparoscopic repair of acutely symptomatic PEH is safe and effective

Abstract: Historically, patients presenting with acute symptoms related to PEH have required open repair, which is associated with significant morbidity and mortality. The acute group was older and sicker than our elective LPEHR patients and had more adverse events resulting in a longer LOS, even when compared with comorbidity-matched elective patients. However, the LOS remained shorter than that reported for open repair and there was no mortality. The recurrence rates in all groups were low and comparable to elective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Fundoplication is part of the typical laparoscopic PEH repair, and many previous studies have demonstrated how safe and practical this type of repair is in treating PEHs [4]. Overall, elective laparoscopic PEH repair has been shown to be associated with decreased recurrence rates, morbidity, length of hospital stay, and need for ICU admission compared to an open approach [5]. In elective surgeries, laparoscopic repair with fundoplication is currently the preferred procedure.…”
Section: Introductionmentioning
confidence: 98%
“…Fundoplication is part of the typical laparoscopic PEH repair, and many previous studies have demonstrated how safe and practical this type of repair is in treating PEHs [4]. Overall, elective laparoscopic PEH repair has been shown to be associated with decreased recurrence rates, morbidity, length of hospital stay, and need for ICU admission compared to an open approach [5]. In elective surgeries, laparoscopic repair with fundoplication is currently the preferred procedure.…”
Section: Introductionmentioning
confidence: 98%
“…4 Because acute complications of PEH, including gastric volvulus and strangulation, are associated with mortality rates as high as 16%, 3 equipoise remains regarding the safety of watchful waiting for symptomatic patients, with many surgeons continuing to advocate for elective intervention. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…pacientes intervenidos tuvieron rangos de edades mayores con múltiples comorbilidades asociadas que influyen, por supuesto, en términos de estancia hospitalaria y morbilidad (34).…”
Section: Consideraciones Técnicas Y Recomendaciones De Los Autoresunclassified
“…Estos resultados contrastan con los reportados por Parker y colaboradores, donde se presentó una mayor estancia hospitalaria y comorbilidades asociadas en pacientes ancianos e intervenidos agudamente (34). Nosotros consideramos que los pacientes ancianos asintomáticos o con sintomatología leve y sin comorbilidades relevantes deben ser evaluados para definir la posibilidad de cirugía.…”
unclassified